Digging deeper: exploring the philosophical roots of heritage interpretation - Landcommanderij Alden Biesen, Bilzen, BE; Interpret Europe - European Association for Heritage Interpretation (2016)
Abstract: Two studies in this e-book explore the philosophical foundations of heritage interpretation and their relations to Europe. What might at a first sight sound like a rather academic question is highly relevant for practice. The philosophies, the paradigms of a discipline, provide orientation for those who work in it. They guide the thinking and thus they guide the direction in which a discipline develops. They shed light on the meaning of the discipline of heritage interpretation within a bigger picture – in our case they explore the question of what heritage interpretation can mean for European societies. The ways in which we perceive natural and cultural heritage today as well as how we think about it originate in European philosophies - despite the fact that heritage interpretation as a professional discipline first developed in North America. Without the Humanist ideas which emerged in Europe during the Renaissance, the Enlightenment movement and the Romantics, which both also influenced European descendants in America, something like heritage interpretation would hardly exist. Furthermore these philosophical currents influenced the paradigms of different approaches to education. Relating heritage interpretation more closely to European philosophies and education traditions should therefore help to understand better how this professional field can be significant for the EU, European states and the people living on this continent. The two studies in this publication approach the problem from two sides: the first by looking back and revealing the historical roots that help understand better today’s practice of heritage interpretation as well as different currents within contemporary interpretation. The second study starts from experiences during a fictive walk which the perceiving and thinking mind can make in order to explore what heritage interpretation can mean for open societies